Patients with sickle cell disease taking hydroxyurea in the Hemocentro Regional de Montes Claros - Santos,Fernanda Kelle de Souza (2011)
BACKGROUND: The development of therapies for sickle cell disease has received special attention, particularly those that reduce the polymerization of hemoglobin S. Hydroxyurea is a commonly used medication because it has the ability to raise levels of fetal hemoglobin, decrease the frequency of vaso-occlusive episodes and thus improve the clinical course of sickle cell disease patients. OBJECTIVE: To study hematological data and the clinical profile of sickle cell disease patients taking hydroxyurea in a regional blood center. METHODS: From the charts of 20 patients with sickle cell anemia, the clinical outcomes and a number of hematological variables were analyzed before and during treatment with hydroxyurea. RESULTS: The patients' ages ranged from 6 to 41 years old, most were dark skinned and there was a predominance of women. The main symptom that defined whether patients were prescribed hydroxyurea was painful crises followed by hospitalizations. During treatment with hydroxyurea there were significant increases in hemoglobin, fetal hemoglobin, mean corpuscular volume and mean corpuscular hemoglobin. The reticulocyte and white blood cell counts dropped significantly with treatment. A positive correlation was found between fetal hemoglobin and mean corpuscular volume before and during treatment. Additionally, a correlation was found between the white blood cell and reticulocyte counts before treatment with hydroxyurea. CONCLUSION: Most patients showed improvements with treatment as demonstrated by increases in hemoglobin, fetal hemoglobin and mean corpuscular volume, as well as by reductions in the reticulocyte and white blood cell counts. Clinically, more than 50% of patients had a significant reduction of events.